2017
DOI: 10.1016/j.ultrasmedbio.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Inflammatory from Fibrotic Ileal Strictures among Patients with Crohn's Disease through Analysis of Time–Intensity Curves Obtained after Microbubble Contrast Agent Injection

Abstract: The aim of the study described here was to assess whether the analysis of time-intensity curves obtained after microbubble contrast agent injection could differentiate inflammatory from fibrotic ileal strictures among patients with Crohn's disease. Sixty-five consecutive patients (40 male and 25 female; mean age ± SD, 42.2 ± 12.22 y) with stricture of the terminal ileal loop from Crohn's disease were scanned after microbubble injection. Time-intensity curves were obtained from quantitative analysis, and peak e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…However, the ability to differentiate fibrotic from inflammatory strictures with CEUS remains controversial. Quaia et al [24] demonstrated that area under the curve and peak enhancement could be used to differentiate predominantly fibrotic from predominantly inflammatory strictures. However, another study using an animal model demonstrated that quantitative perfusion parameters cannot detect the degree of fibrosis in CD when inflammation is also present.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to differentiate fibrotic from inflammatory strictures with CEUS remains controversial. Quaia et al [24] demonstrated that area under the curve and peak enhancement could be used to differentiate predominantly fibrotic from predominantly inflammatory strictures. However, another study using an animal model demonstrated that quantitative perfusion parameters cannot detect the degree of fibrosis in CD when inflammation is also present.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of these two broad categories is recognized as a major role for imaging techniques as management differs. Several investigators have addressed the role of CEUS [ 40 42 ] and also elastography to characterize these strictures with ultrasound [ 42 , 43 ]. Our own study shows that, in patients with chronic stenotic disease, smooth muscle hyperplasia/hypertrophy may contribute more to stricture than fibrosis [ 44 ] similar that to prior study by Baumgart [ 45 ].…”
Section: Indications For Ceus Of the Bowelmentioning
confidence: 99%
“…[ 30 ]. Quaiai et al show differentiation of inflammatory vs fibrotic strictures in which determination of active inflammation would favor the role of medical therapy [ 40 ].…”
Section: Indications For Ceus Of the Bowelmentioning
confidence: 99%
“…8,15,23,24 Recent CEUS studies showed higher values of enhancement intensity and volume kinetic parameters in patients with inflammatory strictures compared to patients with fibrotic strictures. [25][26][27] We also compared the baseline CEUS parameters as a predictor of response to treatment in a small cohort. The values measured with both techniques showed higher PI and AUC parameters in the responders.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found correlations between Doppler measurements and CEUS parameters but not with clinical, laboratory, or endoscopic indices, while others showed correlations between CEUS kinetic parameters, HBI score, CRP levels, and/or endoscopic activity . Recent CEUS studies showed higher values of enhancement intensity and volume kinetic parameters in patients with inflammatory strictures compared to patients with fibrotic strictures …”
Section: Discussionmentioning
confidence: 99%